The mediating role of balanced scorecard between perceived environmental uncertainty and firm performance: (Iraqi case) - Al-Naser, Khalis Hasan Yousif; Mohamed, Rapiah (Panoply Consultancy, 2017)
The purpose of this study is to empirically examine perceived environmental uncertainty (PEU) such as intensity of competition affect firm performance through usage of strategic cost management techniques such as balanced scorecard (BSC). In doing this the study employed a questionnaire survey through which 304 usable responses were analysed using PLS SEM. The findings reveal that PEU (e.g. intensity of competition) positively relates to performance. The result shows a positive relationship between PEU (e.g. intensity of competition) and BSC. The mediating role of BSC is confirmed among the PEU (e.g. intensity of competition) and firm performance. Theoretical and practical implications were drawn.